2009
DOI: 10.1097/ta.0b013e318182afa8
|View full text |Cite
|
Sign up to set email alerts
|

Motion of a Cadaver Model of Cervical Injury During Endotracheal Intubation With a Bullard Laryngoscope or a Macintosh Blade With and Without In-line Stabilization

Abstract: We were unable to demonstrate any significant effect of MILS on the motion of an unstable cervical spine in this cadaver model. The BL appears to be a viable alternative to DL in the setting of an unstable lower cervical spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…39 In fact, at the C3-4 and C4-5 segments, extension of injured cadaver segments during intubation did not seem to exceed the extension observed during intubation of patients with stable cervical spines. 9 Similarly, in 5 of 7 cadaveric studies, 7,15,16,34 subluxation of injured segments during intubation also did not appear to exceed physiologically normal patient values. However, 2 of 7 cadaveric studies found marked (pathological) segmental subluxation during intubation in the presence of severe C5-6 injury (4.8 mm [Donaldson et al 6 ] and 5.7 mm [Prasarn et al 22 ]).…”
Section: Limitations and Implications Of Previous Cadaveric Intubatiomentioning
confidence: 75%
See 2 more Smart Citations
“…39 In fact, at the C3-4 and C4-5 segments, extension of injured cadaver segments during intubation did not seem to exceed the extension observed during intubation of patients with stable cervical spines. 9 Similarly, in 5 of 7 cadaveric studies, 7,15,16,34 subluxation of injured segments during intubation also did not appear to exceed physiologically normal patient values. However, 2 of 7 cadaveric studies found marked (pathological) segmental subluxation during intubation in the presence of severe C5-6 injury (4.8 mm [Donaldson et al 6 ] and 5.7 mm [Prasarn et al 22 ]).…”
Section: Limitations and Implications Of Previous Cadaveric Intubatiomentioning
confidence: 75%
“…19,30 Of particular relevance to our study is that intact (stable) C3-4 extension during Macintosh intubation in cadavers was less than C3-4 extension previously observed in living patients (0.3° ± 3.0° vs 5.1° ± 3.7°, respectively), despite the application of equivalent intubation forces. Of the 6 previous cadaver intubation studies in which the motion of surgically injured subaxial segments during intubation was examined 6,7,15,16,22,34 (see Table 3), only 1 study measured motion of the segment of interest during intubation in the intact state before injury creation. 15 Specifically, Lennarson et al 15 reported a median baseline (intact) C4-5 extension of 0.8° with Macintosh intubation, a value that seems to be less than the C4-5 extension observed in living patients (2.5° ± 3.5°; 9 1.8° ± 3.6°1 4 ).…”
Section: Limitations and Implications Of Previous Cadaveric Intubatiomentioning
confidence: 99%
See 1 more Smart Citation
“…5 Consequently, manual inline stabilization, which does not utilize axial traction, is the method commonly used to reduce intubation-mediated cervical spine motion. Nevertheless, in two cadaver intubation studies, when compared with conventional laryngoscopy, manual inline stabilization did not change the motion of unstable cervical segments, 6,7 and in one study, it increased pathologic motion (subluxation). 5 Increased pathologic motion with manual in-line stabilization is most likely explained as follows: first, by decreasing cervical spine motion, this technique impairs glottic visualization 8,9 ; second, when glottic visualization is impaired, anesthesiologists may apply greater laryngoscope force, either with 9 or without manual in-line stabilization 10 ; and third, in the presence of an unstable segment, greater laryngoscope force application may result in greater segmental motion.…”
Section: To the Editormentioning
confidence: 88%
“…This is consistent with in vitro preconditioning effects. Therefore, we suggest prior cadaver intubation studies which have utilized repeated intubations (4–6 intubations, 9,10,12,15 9–16 intubations, 11,13 or 52 intubations 14 ), but that have not controlled for serial changes in laryngoscope force and/or cervical spine motion, may not accurately predict cervical spine motion.…”
Section: Discussionmentioning
confidence: 99%